Core crush criterion to determine the strength of sandwich composite structures subjected to compression after impact - Castanie, Bruno; Aminanda, Yulfian; bouvet, christophe; barrau, jean-jacques (Elsevier, 2008)
In this study a core crush criterion is proposed to determine the residual strength of impacted sandwich structures. The core of the sandwich is made of a Nomex Honeycomb core and the faces are laminated and remain thin. The mechanism of failure of this kind of structure under post-impact compressive loading is due to interaction between three mechanical behaviors: geometrical nonlinearity due to the skin’s neutral line off-set in the dent area, nonlinear response of the core and damages to the skins. For the type of sandwich analysed in this study, initially the core crushes at the apex of the damage. Using a finite element discrete modelling of the core previously proposed by the authors, the load corresponding to the crushing of the first cell can be computed and it gives the value of the residual strength for our criterion. Some geometric and material hypotheses are assumed in the damaged area mainly based on nondestructive inspection (NDI). The criterion is then applied to tests modelled by Lacy and Hwang [Lacy TE, Hwang Y. Numerical modelling of impact-damaged sandwich composites subjected to compression after impact loading. Compos Struct 2003;61:115–128]. It is shown that the criterion allows a good prediction of the tests except in the case of very small dents. Several sensitivity studies on the assumptions were made and it is shown that using this approach, the criterion is robust.